Adoptive T-cell therapy in the treatment of viral and opportunistic fungal infections. (April 2015) - Mancini, Nicasio; Marrone, Lara; Clementi, Nicola; Sautto, Giuseppe A; Clementi, Massimo; Burioni, Roberto
ABSTRACT : Viral infections and opportunistic fungal pathogens represent a major menace for immunocompromised patients. Despite the availability of antifungal and antiviral drugs, mortality in these patients remains high, underlining the need of novel therapeutic options based on completely different strategies. This review describes the potential of several T-cell-based therapeutic approaches in the prophylaxis and treatment of infectious diseases with a particular focus on persistent viral infections and opportunistic fungal infections, as these mostly affect immunocompromised patients.